2018
DOI: 10.1159/000493500
|View full text |Cite
|
Sign up to set email alerts
|

Ophiopogonin D Reduces Myocardial Ischemia-Reperfusion Injury via Upregulating CYP2J3/EETs in Rats

Abstract: Background/Aims: Epoxyeicosatrienoic acids (EETs) are cytochrome P450 epoxygenase (CYP) metabolites of arachidonic acid and have multiple cardiovascular effects. Ophiopogonin D (OP-D) is an important effective monomeric component in Shenmai injection (SM-I). Both have been reported to have a variety of biological functions, including anti-inflammatory, anti-oxidant, and anti-apoptotic effects. We previously demonstrated that OP-D–mediated cardioprotection involves activation of CYP2J2/3 and enhancement of circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Ginsenoside Rb1 was able to protect cardiomyocytes by activating the PI3K/Akt/mTOR pathway via phosphorylation as shown by Western blot analysis, which was abolished after the application of rapamycin [30]. Ophiopogonin D has multiple biological functions, and studies have shown its ability to inhibit apoptosis by regulating the caspase pathway through arachidonic acid metabolites [27]. Similar to ophiopogonin D, withaferin A improves I/R-injured H9C2 cells viability by inhibiting caspase activity [24].…”
Section: Inhibit Apoptosismentioning
confidence: 97%
“…Ginsenoside Rb1 was able to protect cardiomyocytes by activating the PI3K/Akt/mTOR pathway via phosphorylation as shown by Western blot analysis, which was abolished after the application of rapamycin [30]. Ophiopogonin D has multiple biological functions, and studies have shown its ability to inhibit apoptosis by regulating the caspase pathway through arachidonic acid metabolites [27]. Similar to ophiopogonin D, withaferin A improves I/R-injured H9C2 cells viability by inhibiting caspase activity [24].…”
Section: Inhibit Apoptosismentioning
confidence: 97%
“…Moreover, it has been reported that Akt activation improved contractile function of failing hearts [37,38]. Shreds of evidence have shown that SMI and its ingredients ophiopogonin D activated PI3K/Akt signaling pathway in myocardial ischemia-reperfusion injury [39]. Our previous study suggested that ginsenoside Rg3 could promote cell viability and attenuate DOX-induced oxidative damage and apoptosis through Akt activation [40].…”
Section: Discussionmentioning
confidence: 95%
“…This molecule has been shown to have anti-apoptotic, antioxidant, and anti-inflammatory properties ( Huang et al, 2015 ; You et al, 2016 ). The left anterior descending coronary artery was also occluded in rats to create the MI/R model for studying the antioxidants OP-ED and SM-I ( Huang et al, 2018 ). An infarct is reduced in size, and heart architecture is improved by using OP-ED and SEM-I to protect cardiac function from MI/R.…”
Section: Essential Bioactive Compounds and Ingredients Of Traditional...mentioning
confidence: 99%